Modulating the poly-l-lysine structure through the control of the protonation–deprotonation state of l-lysine - Luigi Stagi; Martina Sini; Davide Carboni; Roberto Anedda; Giuliano Siligardi; Tiberiu-Marius Gianga; Rohanah Hussain; Plinio Innocenzi (Scientific Reports, 2022)
Abstract Designing the architecture of l-lysine-based polymeric structures is a highly challenging task that requires careful control of the amino acid reactive groups. Conventional processes to obtain branched polylysine need several steps and the addition of specific catalysts. In the present work, to gain a better understanding and control of the formation of l-lysine-based polymers, we have investigated the correlation between the protonation state of l-lysine and the corresponding hydrothermally grown structures. The samples have been characterized by combining optical spectroscopies, such as UV–Vis, fluorescence, and synchrotron radiation circular dichroism with structural analysis by Nuclear Magnetic Resonance, Fourier Transform Infrared spectroscopy, and dynamic light scattering. We have observed that aqueous precursor solutions with alkaline pHs promote the formation of branched structures. In contrast, high pHs favour the reactivity of the ε-amino groups leading to linear structures, as shown by circular dichroism analyses. On the other hand, acidic conditions trigger the branching of the amino acid. Interestingly, the polymeric forms of l-lysine emit in the blue because the increasing number of intermolecular hydrogen bonds promote the intermolecular charge transfer responsible for the emission. Understanding the correlation between the l-lysine charged states and the polymeric structures that could form controlling the protonation–deprotonation states of the amino acid opens the route to a refined design of polypeptide systems based on l-lysine.